Huperzine A and Its Neuroprotective Molecular Signaling in Alzheimer's Disease - Friedli, Maria Jesus; Inestrosa, Nibaldo C. (My University, 2021)
Huperzine A (HupA), an alkaloid found in the club moss Huperzia serrata, has been used for centuries in Chinese folk medicine to treat dementia. The effects of this alkaloid have been attributed to its ability to inhibit the cholinergic enzyme acetylcholinesterase (AChE), acting as an acetylcholinesterase inhibitor (AChEI). The biological functions of HupA have been studied both in vitro and in vivo, and its role in neuroprotection appears to be a good therapeutic candidate for Alzheimer&PRIME;s disease (AD). Here, we summarize the neuroprotective effects of HupA on AD, with an emphasis on its interactions with different molecular signaling avenues, such as the Wnt signaling, the pre- and post-synaptic region mechanisms (synaptotagmin, neuroligins), the amyloid precursor protein (APP) processing, the amyloid-beta peptide (A beta) accumulation, and mitochondrial protection. Our goal is to provide an integrated overview of the molecular mechanisms through which HupA affects AD.
Keywords: neurodegenerative diseases; huperzine; achei; alzheimer's disease; therapeutic potential; neuroinflammation